Efektivitas Penegakan Hukum Penyelesaian Sengketa Konsumen Di Sumatera Barat - Syam, Misnar; Fitri, Devianty (Faculty of Law, Andalas University, 2025)
Law enforcement in resolving consumer disputes is a repressive legal protection. This repressive protection aims to restore consumer rights or resolve disputes when there is a violation of consumer rights or disputes between consumers and business actors. Law enforcement in resolving consumer disputes in West Sumatra has not achieved the desired effectiveness, even though there is Law Number 8 of 1999 concerning Consumer Protection (hereinafter referred to as UUPK) which regulates the resolution of consumer disputes. This is because there are still many consumer losses that cannot be recovered or consumer rights are not fulfilled because the resolution of their disputes has not been fully in accordance with what is expected in the law. The formulation of the problem in this paper is how effective is the resolution of consumer disputes in West Sumatra? The method used in this study is empirical juridical, using primary data and supported by secondary data. The approach used is a non-doctrinal approach. The nature of the research is descriptive. The data collection uses field studies, namely by interviewing respondents and informants which are strengthened by document studies. Data processing is by editing and analysis using qualitative juridical analysis. The conclusion of this study is that consumer dispute resolution in West Sumatra is not yet effective, where consumers have not received justice.